Six new bacterial species isolated from the phycosphere of marine macroalgae: a joint analysis based on taxonomy and polysaccharide utilization loci - De-Chen Lu; De-Chen Lu; Ying Yuan; Xin-Yun Tan; Le Liu; Jin-Hao Teng; Xue Cui; Tian-He Liu; Tian-He Liu; Jing Zhang; Zong-Jun Du; Zong-Jun Du; et al. (Frontiers in Microbiology, 2025)
Marine macroalgae-associated Bacteroidota play crucial roles in global carbon cycling through polysaccharide degradation, yet their taxonomic and functional diversity remains understudied. Here, we describe six novel species (strains 3-376T, 4-2040T, 2-473AT, 4-528T, 4-911T and 463T) within the families Flavobacteriaceae, Crocinitomicaceae, and Cytophagaceae isolated from macroalgal surfaces in the coastal area of Weihai, China. Metagenomic read recruitment and 16S rRNA abundance analyses demonstrated host-specific associations. Integrative taxonomic analyses, including phylogenomics (120 conserved proteins), 16S rRNA sequencing, and chemotaxonomy (e.g., MK-6 quinones, phosphatidylethanolamine lipids, and iso-C15:0 fatty acids), confirmed their novel status, with average amino acid identity (AAI), percentage of conserved proteins (POCP) distinguishing them from related taxa. Genomes (3.3–7.1 Mb; G + C 31.7–45.3%) revealed diverse polysaccharide utilization loci (PULs) targeting algal glycans like laminarin, alginate, and sulfated polymers (ulvan, chondroitin sulfate). Cytophagaceae 463T harbored the richest CAZyme/PUL repertoire (131 CAZymes, 15 PULs), while Crocinitomicaceae 4-911T lacked PULs, highlighting family-level specialization. This study expands the known diversity of core phycosphere Bacteroidota, linking PUL evolution to habitat specialization. The novel species’ distinct degradative capacities underscore their ecological roles in algal carbon processing and potential for biotechnological applications. Our integrated taxonomy-genomics approach advances understanding of microbial contributions to marine ecosystem dynamics.